Aerosol formation pathways from aviation emissions. (1st February 2022) - Prashanth, Prakash; Eastham, Sebastian D; Speth, Raymond L; Barrett, Steven R H
Abstract: Aviation emissions are responsible for an estimated 24, 000 premature mortalities annually and 3.5% of anthropogenic radiative forcing (RF). Emissions of nitrogen and sulfur oxides (NOx and SOx ) contribute to these impacts. However, the relative contributions and mechanisms linking these emissions to formation and impacts of secondary aerosols (as opposed to direct aerosol emissions) have not been quantified, including how short-lived aerosol precursors at altitude can increase surface-level aerosol concentrations. We apply global chemistry transport modeling to identify and quantify the different chemical pathways to aerosol formation from aviation emissions, including the resulting impact on radiative forcing. We estimate a net aerosol radiative forcing of –8.3 mWm −2, of which –0.67 and –7.8 mWm −2 result from nitrate and sulfate aerosols respectively. We find that aviation NOx causes –1.7 mWm −2 through nitrate aerosol forcing but also –1.6 mWm −2 of sulfate aerosol forcing by promoting oxidation of SO2 to sulfate aerosol. This accounts for 21% of the total sulfate forcing, and oxidation of SO2 due to aviation NOx is responsible for 47% of the net aviation NOx attributable RF. Aviation NOx emissions in turn account for 41% of net aviation-aerosol-attributable RF (non-contrail). This is due to ozone-mediated oxidation of background sulfur and the 'nitrate bounce-back' effect, which reduces the net impact of sulfur emissions. The ozone-mediated mechanism also explains the ability of cruise aviation emissions to significantly affect surface aerosol concentrations. We find that aviation NOx emissions cause 72% of aviation-attributable, near-surface aerosol loading by mass, compared to 27% from aviation SOx emissions and less than 0.1% from direct emission of black carbon. We conclude that aviation NOx and SOx emissions are the dominant cause of aviation-attributable secondary inorganic aerosol radiative forcing, and that conversion of background aerosol precursors at all altitudes is amplified by enhanced production of aviation attributable oxidants at cruise altitudes.